The Emphatic Compound Adjectives in Arabic - Ehsan Esmaeeli Taheri (دراسات في اللغة العربيّة وآدابها)
Â  Most books of Arabic syntax and morphology refer only to 15 metrical types of emphatic adjectives derived only from three-letter verbs. They judge any formation of adjectives from other types of verbs as ungrammatical constructions. However, a study of Arabic texts and dictionary shows that Arab speakers, because of their communicative need for emphatic constructions derived from intransitive verbs, form useful emphatic constructions from such verbs similar to making compound comparative forms and exclamatory forms, i.e., they use an emphatic word (âmanyâ, âmuchâ, âintensiveâ) the infinitive of the intended verb. This construction, which is frequently used in traditional and modern Arabic texts, has been neglected by traditional and contemporary syntacticians. This article presents evidence for the existence of such emphatic forms and considers them of two types: basic and derivative. The basic forms are confined to 10 to 15 metrical types and are not rule governed. The derivative forms are made by family resemblance from almost any infinitive. The author of this article believes that the conditions for constructing emphatic forms, comparative adjectives and exclamatory forms â whether basic or derivativeâare quite the same.